2011
DOI: 10.1111/j.2042-3306.2010.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of equine bone marrow and adipose tissue‐derived mesenchymal stromal cells

Abstract: To provide data to better understand AT-MSCs and BM-MSCs behaviour in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
56
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 47 publications
8
56
2
1
Order By: Relevance
“…In addition, HAMα cells had excellent proliferative ability, and their average population doubling time was 46.53 ±5.16 h in passage 5. These results indicated that HAMα cells possessed similar properties to MSCs derived from other tissues in previous studies [12,20,22,25,26]. We are currently in the process of obtaining more series of HAMα cells with improved efficiency.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, HAMα cells had excellent proliferative ability, and their average population doubling time was 46.53 ±5.16 h in passage 5. These results indicated that HAMα cells possessed similar properties to MSCs derived from other tissues in previous studies [12,20,22,25,26]. We are currently in the process of obtaining more series of HAMα cells with improved efficiency.…”
Section: Discussionsupporting
confidence: 72%
“…HAMα cells derived from all the donors showed excellent potential for osteogenic differentiation. Although direct comparative study was not performed in this study, the differentiation ability of HAMα cells was comparable to that of MSCs derived from other tissues, with regard to ALP activity and OCN gene expression [22,23,[25][26][27][28]. In MSCs derived from the bone marrow, the effect of donor age or cell generation time on cell proliferation and differentiation has been discussed [12,14,15,25].…”
Section: Discussionmentioning
confidence: 61%
“…Rabbit serum has a high content in free fatty acids, which are putative ligands of peroxisome proliferator-activated Receptor gamma and may thus enhance adipogenesis. Recently, Ranera et al [47], comparing different induction media for adipogenic differentiation of equine MSCs, found that only the medium supplemented with 15% rabbit serum was able to induce adipogenic differentiation. However, other authors demonstrated that incubation with rabbit serum for a long period, however, can lead to cell detachment [48].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, several markers have been tested and used, such as the positive markers CD44, CD90 CD29 [11,15,17,20], CD105 [21-23], MHC-I [5,15,20] and the negative markers CD14 [17], CD34 [21,23], MHC-II [5,17,20,23,24], CD45 [21,24], based on minimal criteria established by the International Society for Cellular Therapy (ISCT) to define human MSCs [25] and adipose-tissue derived stromal/stem cells [26]. …”
Section: Introductionmentioning
confidence: 99%